Biheterocyclic ligands: synthesis, characterization and coordinating properties of bis(4-amino-5-mercapto-1,2,4-triazol-3-yl) alkanes with transition metal ions and their thermokinetic and biological studies - Al-Maydama, Hussein; Al-Ansi, Tajedin Yahya; Jamil, Yasmin M. S.; Ali, A. H. (Eclética Química, 2008)
The Co(II), Ni(II) and Cu(II) metal ions complexes of Bis(4-amino-5-mercapto-1,2,4-triazol-3-yl) alkanes (BATs) have been prepared and characterized by elemental analysis, conductivity measurements infrared, magnetic susceptibility, the electronic spectral data and thermal studies. Based on spectral and magnetic results, the ligands are tetradentate coordinating through the N and S-atoms of BATs; six-coordinated octahedral or distorted octahedral and some times four-coordinated square planar were proposed for these complexes. Activation energies computed for the thermal decomposition steps were compared. The ligands and their metal complexes were tested in vitro for their biological effects. Their activities against two gram-positive, two gram-negative bacteria and two fungal species were found to vary from moderate to very strong.